Higher infliximab trough levels are associated with perianal fistula healing in patients with Crohn's disease. Issue 7 (17th February 2017) - Yarur, A. J.; Kanagala, V.; Stein, D. J.; Czul, F.; Quintero, M. A.; Agrawal, D.; Patel, A.; Best, K.; Fox, C.; Idstein, K.; Abreu, M. T.
Summary: Background: Infliximab has been found to be efficacious in the treatment of fistulas in the setting of Crohn's disease, even though some patients do not benefit from therapy. Aim: To assess the correlation between perianal fistula healing and trough levels of infliximab. Methods: In this cross‐sectional study, we identified patients with Crohn's disease who had perianal fistulas and were treated with infliximab for at least 24 weeks. We excluded patients who underwent a faecal diversion procedure or proctectomy. Predictive variables included demographics, disease phenotype, disease activity, infliximab levels, anti‐infliximab antibodies. The primary outcome was fistula healing defined as the absence of drainage. The secondary outcome was complete fistula closure and mucosal healing. Results: 117 patients were included. Patients with fistula healing had significantly higher median serum infliximab levels when compared to those with active fistulas [15.8 vs. 4.4 μg/mL, respectively ( P < 0.0001)]. There was an incremental gain in fistula healing with higher infliximab levels. The AUC for the association between fistula healing and infliximab levels was 0.82 ( P < 0.0001), while the AUC for the association of infliximab levels and fistula closure was 0.69 ( P = 0.014). Patients with anti‐infliximab antibodies had a lower chance of achieving fistula healing (OR: 0.04 [95%CI: 0.005–0.3], P < 0.001). Conclusions: There is a significant association between serum infliximab levels and rates of fistula healing. Achieving infliximab levels ≥10.1 mcg/mL in patients with Crohn's disease and perianal fistulas may improve outcomes as part of a treat‐to‐target strategy. Abstract : Linked Content This article is linked to Mitrev et al paper. To view this article visithttps://doi.org/10.1111/apt.14020 .